The long-term effects of fire frequency and season on the woody vegetation in the Pretoriuskop Sourveld of The Kruger National Park - O’Regan, Sean Patrick (My University, 2007)
O’Regan SP, 2005. The long-term effects of fire frequency and season on the woody vegetation in the Pretoriuskop sourveld of the Kruger National Park. MSc Dissertation, University of the Witwatersrand, Johannesburg. The role of fire in the management of conservation areas has historically been a contentious issue in which traditional agricultural principles and ever-changing conservation principles tend to collide. The Kruger National Park (KNP) in the early 1950s was no exception where the appropriate use of fire and its ecosystem consequences were hotly debated. The controversy surrounding the management of fire in the KNP highlighted the significant lack of understanding of fire and its role in the ecosystem and because of this controversy, the Experimental Burn Plot (EBP) experiment was established in 1954. The EBP experiment comprised 12 treatments, and a pseudo-randomised block design was used in which the 12 fire treatments were replicated four times each in four of the six major vegetation zones identified at the time. The EBP experiment originally comprised 192 experimental plots approximately 7 Ha in size each and covered approximately 12 km2 in the KNP. The twelve fire treatments were an annual burn in August, biennial and triennial burns in February, April, August, October, and December, and a control on which fire was excluded. Despite having been plagued with negative assessments from internal and external researchers from its inception, the EBP experiment was meticulously maintained, and it has now become a valuable research asset in the KNP. Four replicates of twelve plots each were located in the Pretoriuskop sourveld landscape of the KNP. These replicates were named Fayi, Kambeni, Numbi, and Shabeni after nearby landmarks. The Pretoriuskop region is a moist infertile mesic-savanna, which experiences on average 744mm of rain annually. The dominant tree species in Pretoriuskop are Dichrostachys cinerea and Terminalia sericea and the dominant grass species is Hyperthelia dissoluta. A baseline survey of the woody vegetation was done on all the Pretoriuskop plots in 1954 by HP Van Der Schijff. A second survey of the woody vegetation on all the Pretoriuskop plots was done in 1996 by SP O’Regan. This provided a 42-year period of treatment application over which the effects of fire frequency and season on the woody vegetation of the Pretoriuskop region were studied. The aim of this study was to investigate the long-term effects of the twelve fire treatments on the density, structure, and species composition of the woody vegetation in Pretoriuskop. The objectives of this study were: 1. To carry out a complete re-survey of the trees and shrubs on the Pretoriuskop EBPs using similar methods as those used in the baseline survey in 1954. 2. To capture into a digital format pertinent woody vegetation survey data from surveys that had been conducted on the Pretoriuskop EBPs between 1954 and 1996. 3. To compare the density, structure, and composition of the woody vegetation on the Pretoriuskop EBPs between 1954 and 1996, to determine the effects of fire on the woody vegetation of Pretoriuskop. 4. To investigate the history of the Kruger National Park Experimental Burn Plots experiment. The four replicates in the Pretoriuskop region were found generally to have very similar woody vegetation traits (density, species composition, and structural composition). However, the EBPs were established and surveyed in two distinct phases, the first phase comprised the control, August Annual, and the Biennial plots, and the second phase comprised the Triennial plots. The baseline structural composition of the plots established in the first phase was different from the structural composition of the plots in the second phase. Furthermore, the Pretoriuskop EBPs are located in two distinct vegetation types, namely the open and the closed Terminalia sericea \ Combretum woodlands of the Pretoriuskop region. The Numbi and Shabeni replicates are in the open Terminalia sericea \ Combretum woodlands, and the Kambeni and Fayi replicates are in the closed Terminalia sericea \ Combretum woodlands. It was found that the species composition of the plots was influenced by the location of the plots in the different vegetation types. The exclusion of fire in the Pretoriuskop sourveld results in an increase in the density of the overstorey and understorey woody vegetation, and an increase in the number of species, species diversity, and species evenness. This is because fire sensitive and fire intolerant woody species become more abundant as the period between fires increases. In Pretoriuskop, there is no evidence of relay floristic succession, because fire sensitive and fire intolerant woody species do not replace fire tolerant species. Instead, the floristic succession is accumulative and fire tolerant, fire sensitive, and fire intolerant woody species coexist as the period between fires increases. Woody species tolerant of frequent fires in Pretoriuskop are Albizia versicolor, Catunaregam spinosa, Lonchocarpus capassa, Pavetta schumanniana, Senna petersiana, Strychnos madagascariensis, and Turraea nilotica. Woody species that are sensitive or intolerant of fire in Pretoriuskop are Acacia swazica, Bauhinia galpinii, Combretum mossambicense, Commiphora neglecta, Croton gratissimus, Dalbergia melanoxylon, Diospyros lycioides, Diospyros whyteana, Euclea natalensis, Hyperacanthus amoenus, Kraussia floribunda, Ochna natalitia, Olea europaea, Psydrax locuples, Putterlickia pyracantha, Tarenna supra-axillaris, and Zanthoxylum capense. Dichrostachys cinerea and Terminalia sericea were found to dominate in areas that had been burnt frequently as well as areas where fire has been excluded. The change in the density of the woody vegetation as the inter-fire period increases is not linear but rather J shaped with an initial decrease in the density as the inter-fire period increases from 1 year to 3 years. This initial decrease in density is the result of a loss of very short (<1m tall) woody individuals. In contrast, there is no initial decrease in the number of tree equivalents (phytomass) of the woody vegetation as the inter-fire period increases. After the initial decrease in the density of the woody vegetation, the density increases as the inter-fire period increases beyond 3 years. Generally in Pretoriuskop, post fire age of the vegetation was found to be an important factor affecting the structure of the woody vegetation, and as the inter-fire period increases the number of structural groups, the structural diversity, and the structural evenness of the woody vegetation increases. As the inter-fire period increases the number of single-stem individuals relative to the number of multi-stem individuals increases, and the average height of the woody vegetation increases. The findings regarding the effects of fire frequency on the Pretoriuskop EBPs were similar to the findings on other fire experiments in mesic African savannas. The finding on the Pretoriuskop EBPs differed from the findings in other fire trials that were in arid savannas in Africa. Generally, the exclusion of fire in moist savannas (> 600 mm of rain annually) results in the woody vegetation becoming denser, while the exclusion of fire in arid to semi-arid savannas (< 600mm of rain annually) does not result in the woody vegetation becoming denser. In Pretoriuskop, fires occurring in summer between December and February have a different impact on the density, species composition, and structure of the woody vegetation than fires occurring in winter between August and October. Furthermore, fires occurring in April have a different impact on the density, species composition, and structure of the woody vegetation in Pretoriuskop. Woody vegetation burnt by summer fires is denser than woody vegetation burnt by winter fires. The number of species and species diversity of the woody vegetation is also higher in vegetation burnt by summer fires in comparison with vegetation burnt by winter fires. The density and species composition of woody vegetation in areas that have been burnt in summer fires is more similar to areas where fire has been excluded than to areas that have been burnt in winter fires. The woody species associated with vegetation burnt in summer fires and where fire has been excluded are Euclea natalensis, Antidesma venosum, Diospyros lycioides, Phyllanthus reticulatus, Grewia flavescens, Grewia monticola, Ochna natalitia, Peltophorum africanum, Rhus pyroides, Diospyros mespiliformis, Rhus transvaalensis, Securinega virosa, Putterlickia pyracantha, Rhus pentheri, Commiphora neglecta, Heteropyxis natalensis, and Olea europaea. Structurally the average height of the woody vegetation is taller in areas burnt by winter fires than in areas burnt by summer fires. The woody vegetation in areas burnt in summer fires have more single-stem individuals relative to multi-stem individuals than in areas burnt in winter fires. The structural composition of areas burnt in summer fires is more similar to areas where fire has been excluded than with areas burnt in winter fires. The structure of the woody vegetation in areas burnt in winter fires is generally dominated by multi-stem individuals that are 0-1m tall or 3-5m tall. The structure of the woody vegetation in areas burnt in summer fires or where fire has been excluded is dominated by both single-stem and multi-stem individuals of all heights and basal diameters. Findings regarding the effect of early dry season fires (April) in comparison with late dry season fire (August) on the woody vegetation are consistent with the findings on other fire trails in Africa. However, a comparison of all the fire-timing treatments between the Pretoriuskop and Satara EBPs in the KNP reveals that the timing of fires affects the woody vegetation differently in different areas even when the affects at certain times appear similar. The data collected on the Pretoriuskop EBPs reveals that there have been significant changes in the woody vegetation in Pretoriuskop between 1954 and 1996. The density of the woody vegetation increased between 1954 and 1996 by almost 200%. The number of species and the species diversity of the woody vegetation also increased between 1954 and 1996. In 1954, there were approximately equal numbers of single-stem and multi-stem individuals, while in 1996 there were more multi-stem individuals than single-stem individuals. The increase in atmospheric CO2 levels between 1954 and 1996 is believed to have been a factor that has driven the changes in the woody vegetation of Pretoriuskop between 1954 and 1996.
Student Number : 9008538J - MSc Dissertation - School of Biology - Faculty of Science
Keywords: Fire; Savanna; Kruger National Park; KNP; Pretoriuskop; Woody Vegetation; Trees; Shrubs; Experimental Burn Plots; EBP; Long-term; Ecological experiment; Fire frequency; Fire timing; Fire exclusion; Density; Structure; Species diversity; Mesic savanna; Sourveld; Atmospheric CO2